Evaluation of Novel Calcium Silicate-Based Sealers Reinforced with Bioactive Glass - Divya Batra; Surya Dahiya; Sunil Kar; Ambuj Arora; Ashtha Arya; Ataul H. Imran (Journal of Pharmacy and Bioallied Sciences)
Background: Calcium silicate-based sealers have gained significant attention in endodontics due to their biocompatibility, bioactivity, and sealing ability. Incorporating bioactive glass into these sealers could potentially enhance their physicochemical and biological properties, providing improved clinical outcomes. Materials and Methods: Three experimental sealer groups were prepared: group A (calcium silicate-based sealer without reinforcement), group B (calcium silicate-based sealer with 10% bioactive glass), and group C (calcium silicate-based sealer with 20% bioactive glass). The sealers were assessed for their setting time, compressive strength, solubility, and bioactivity. Bioactivity was evaluated by immersing the sealers in simulated body fluid and analyzing hydroxyapatite formation using scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). Statistical analysis was conducted using ANOVA with a significance level of P < 0.05. Results: Group C demonstrated the shortest setting time (20 ± 1.5 minutes) compared to group B (25 ± 1.2 minutes) and group A (30 ± 1.8 minutes). Compressive strength was significantly higher in group C (80 ± 5 MPa) than in group B (65 ± 4 MPa) and group A (50 ± 3 MPa). Solubility was lowest in group C (2.5 ± 0.3%) and highest in group A (4.5 ± 0.4%). SEM and EDS analysis revealed a greater formation of hydroxyapatite on the surface of group C, indicating superior bioactivity. Conclusion: The addition of bioactive glass to calcium silicate-based sealers significantly improved their mechanical properties, reduced solubility, and enhanced bioactivity. The findings suggest that these reinforced sealers could be promising candidates for endodontic applications, providing improved long-term sealing and biological outcomes.